Determinan Kepatuhan Wajib Pajak Pelaku UMKM: Peran Literasi Perpajakan, Sanksi Pajak, dan Digitalisasi Layanan Pajak - Rizki Muti Agustiani (Graha Mitra Edukasi, 2026)
This study aims to examine the influence of tax literacy, tax sanctions, and the digitalization of tax services on the tax compliance of Micro, Small, and Medium Enterprises (MSMEs). The study is motivated by the relatively low level of tax compliance among MSMEs despite their substantial contribution to Indonesia's national economy. A quantitative approach with an explanatory research design was employed. The study utilized primary data collected through questionnaires distributed to 100 MSME owners in Makasar District, East Jakarta Administrative City, selected using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results of the outer model evaluation indicate that all measurement indicators satisfy the required validity and reliability criteria, while the inner model evaluation demonstrates that the proposed model possesses adequate predictive capability. Hypothesis testing reveals that tax literacy has a positive and significant effect on taxpayer compliance. Tax sanctions also have a positive and significant influence on taxpayer compliance by encouraging adherence to prevailing tax regulations. Furthermore, the digitalization of tax services significantly and positively affects taxpayer compliance by providing greater convenience, efficiency, and effectiveness in fulfilling tax obligations. This study contributes empirically by reinforcing the applicability of the Theory of Planned Behavior, Deterrence Theory, and the Technology Acceptance Model in explaining the tax compliance behavior of MSME taxpayers. Moreover, the findings are expected to provide valuable insights for the Directorate General of Taxes in formulating policies focused on improving tax literacy, strengthening the effective enforcement of tax sanctions, and optimizing digital tax services to enhance MSME taxpayer compliance.